Harnessing the energy of the corporate sector to end TB: BE health - Anne Marie Bettex; Hannah Monica Yesudian Dias; Giovanni B. Migliori; Mario C. Raviglione (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2020)
The World Health Organization (WHO) estimates that 3 million people with TB are missing’ from the official information system. They remain often undiagnosed and untreated or are managed outside the national TB programme structure by various care providers (including the private for-profit sector) and are not notified. The care provided to these patients is often sub-standard, not aligned with national and international guidelines, and un-regulated. WHO has repeatedly underlined the importance of collaborating with the private sector to improve prevention, diagnosis and treatment of TB, Private organisations could join public healthcare institutions’ efforts and expand their breadth of interventions to preventive interventions and play a complementary role to the public healthcare systems. Having access to a large scope of employees, customers, suppliers and other stakeholders, corporations should indeed be able to undertake prevention activities utilising their capacity to generate the necessary resources.BE Health is an example of such a private initiative. It was established to build bridges between the workplace and the local communities aiming to empower high-risk populations to address their own major killers such as TB, HIV/AIDS and malaria, within the framework and targets of the United Nations Sustainable Development Goals. In collaboration with healthcare experts, BE Health decided at first to build awareness and spread information on health at the workplace. The approach focused on training newly-formed peer health educators capable of transferring knowledge to their local community. BE Health managed to create a solid network of peer health educators (selected among skilled employees) and community health volunteers selected among slum dwellers) operating in the metropolitan areas of Bangkok and Djibouti and focused on TB and HIV prevention among local impoverished communities.Between 2013 and 2019, 51 peer Health Educators were trained, over 213 health promotion activities were organised at the workplace and more than 4,000 employees were reached through prevention activities, 730 community visits were conducted, over 1900 households were screened for TB and/or HIV with more than 22,000 people reached directly by prevention activities.Similar third party approaches need to be further assessed, harnessed and expanded to complement efforts of the public health sector.